Neurofeedback training and motor learning: the enhanced sensorimotor rhythm protocol is better or the suppressed alpha or the suppressed mu? - Afrash, S.; Saemi, E.; Gong, A.; Doustan, M. (BMC Sports Science, Medicine and Rehabilitation, 2023)
A large number of previous studies have examined how different neurofeedback-based techniques may influence motor learning. However, only a few studies attempted to compare the effects of these different techniques on motor learning. Therefore, the present study attempts to examine the effects of neurofeedback training on motor learning in novice golfers, using three protocols, namely enhanced sensorimotor rhythm (SMR) at Cz, suppressed alpha waves at Fz, and suppressed mu waves at Cz. The participants were 64 adults (32 females; mean age = 22.31 ± 2.25 years). The study consisted of a pretest stage (day 1), intervention (6 sessions, over two weeks, 3 sessions per week), short-term retention (one day after intervention), and long-term retention (two weeks after intervention); in the pretest and short-term and long-term retention, motor performance for golf putting (12 trials) as well as amplitudes of SMR wave at Cz, alpha at Fz, and Mu at Cz were recorded. During each intervention session, the participants in three neurofeedback groups and a sham group first performed neurofeedback training (enhanced SMR at Cz, suppressed alpha at Fz, and suppressed Mu at Cz) for 20 min. Then, the participants in all groups performed three blocks of 12 trials consisting of golf putting training. The results indicated no difference between the sham and the experimental groups in the acquisition stage, as individuals in all groups experienced similar improvement in putting accuracy. However, in the short-term retention, all the three neurofeedback groups outperformed the sham group, although in the long-term retention, only the SMR group and the Alpha group showed a better performance than the sham group while the Mu group did not exhibit a notably better performance than the sham group. Our results also showed significant variations in the amplitudes of the SMR, alpha, and mu waves depending on the neurofeedback intervention provided, while no significant variation was observed in the sham group. Based on these results, it is recommended that coaches should make further use of enhanced SMR at Cz or suppressed alpha at Fz as their neurofeedback interventions to facilitate longer-term motor learning in golfers.